Begonia limprichtii Irmsch. (Begoniaceae) – a new record for India - Borah, Dipankar; Taram, Momang; Wahlsteen, Eric ; 0000-0001-8283-1112 (Biodiversity Research and Conservation, 2021)
Begonia limprichtii (Begoniaceae) is reported from India for the first time. It belongs to the section Platycentrum and is similar to B. thomsonii, but is overall less hairy with ovary nearly glabrous (versus villous) and upper ovary wing beaked and rounded (versus triangular).